Christianity in a revolutionary age ; v. 2 a history of Christianity in the nineteenth and twentieth centuries - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1970)
Includes bibliographical references and index.
Contents : v. 2 : The nineteenth century in Europe : the Protestant and Eastern churches. Includes bibliographical references and index.
First edition published 1958, New York, Harper and Row.
Keywords: Church history -- Europe -- 19th century